Scottish young people's post-school destinations 1977-83 - Shelly, Michael Anthony (The University of Edinburgh, 1988)
In this Thesis data from The Scottish Education Data Archive, relating to the 1977, 1979, 1981 and 1983 Scottish School Leavers Surveys, are used in order to examine Scottish young people's post-school destinations. The major change, over the period 1977-83, was a dramatic decline in the proportion entering employment. Most of the material in the Thesis is directly concerned with school leavers' employment.

In the introductory chapter, the scene is set for the rest of the Thesis and three proposed explanations of the decline in youth employment are critically reviewed; they are: the real wage, the demand deficiency and the structural hypotheses. The introductory chapter concludes with a discussion of the Scottish Education Data Archive. The second and third chapters contain an examination of the changes in Scottish school leavers' industrial and occupational distributions of employment, respectively. The fourth chapter examines the role played by changes in the industrial distribution of school leavers' employment in determining the changes in their occupational distribution of employment. The fifth chapter examines the extent to which the decline in school leavers' employment was disproportionately large, compared to the decline in all ages' employment, and the extent to which this resulted from either structural change or school leavers' particularly vulnerable labour market position. The sixth chapter examines the question of whether the bottom has dropped out of the market for school leavers' labour. The seventh chapter contains an econometric examination of the role played by a measure of school leaver's employment prospects, amongst other factors, in influencing their decisions as to whether to continue into full-time tertiary education.